PROTOTYPE SISTEM KETERSEDIAAN DAN KAPASITAS TEMPAT PARKIR MOBIL BERBASIS ARDUINO UNO - Arya Dwitama; Mariza Wijayanti; Meta Meysawati; Fauziah Fauziah; Yuli Fitriyani; Dina Agusten (Jurnal Ilmiah Teknik, 2025)
The current parking system still uses a manual parking system, vehicle owners still have difficulty finding an empty parking space because they have to go around the parking area so it is less efficient and takes a long time. This study aims to help car drivers save time in finding parking locations and knowing the availability of parking spaces. In this study, there are two types of input used: infrared sensors, which function to measure the capacity of the parking space, and RFID sensors, which are used to detect cards. The data processing process is carried out using Arduino Uno, while the LCD is used to display the number of available parking slots and the location of the slot. In addition, the servo motor functions to open the barrier. This system operates in a way, when a car enters and attaches a registered card, the servo motor will open, and the number of parking slots will decrease. The driver then selects a parking slot, which will be automatically marked as "full" on the LCD screen. When the infrared sensor detects a car that wants to exit, the servo motor will open again, and the number of parking slots on the LCD will increase.